Patient-reported quality of life and adherence outcomes after integrating exclusive liquid meal replacement in patients with head and neck cancer undergoing chemoradiation: results from a phase II study - Valle, Luca F.; Chu, Fang-I; Wang, Xiaoyan; Erman, Andrew; Hernandez, Jackie; Kaoh, Elizabeth; Edgar, Nicolas; Raldow, Ann C.; Wong, Deborah J.; Steinberg, Michael L.; Kishan, Amar U.; Chin, Robert K.; et al. (Frontiers in Oncology, 2025)
ObjectivesPreventing malnutrition during chemoradiation (CRT) for head and neck cancer is critical maximizing quality of life (QOL). We sought to assess patient-reported QOL outcomes after integrating exclusive liquid meal replacement with Soylent, a novel meal replacement agent, in patients with head and neck cancer undergoing CRT.MethodsPatients undergoing definitive or adjuvant concurrent CRT for locally advanced head and neck cancer enrolled on our single-institution, prospective phase II protocol evaluating nutritional replacement with Soylent. Patients who reached 5% body weight loss during CRT were transitioned to Soylent meal replacement for all nutritional needs. Patients who reached 10% body weight loss were recommended for gastrostomy tube (G-tube) placement. UW-QOL and FACT-H&N questionnaires assessed patient-reported QOL prior to the receipt of CRT and following conclusion of CRT. Paired t-test or Wilcoxon signed-rank test were performed to assess for differences between scores at each follow-up time point and baseline.ResultsOf the 60 enrolled patients, 51/60 (85%) lost 5% of their pre-treatment body weight. Among these patients, 48/51 (94%) were successfully transitioned to Soylent. 22/48 patients subsequently lost 10% of their pre-treatment body weight, and 3/22 (14%) underwent G-tube placement with the remainder declining. This resulted in an overall G-tube rate of 5%. Among the 41 patients evaluable for QOL data, the nadirs for overall and health-related UW-QOL were reached at 1 month and rebounded to exceed baseline by 6 months. FACT-H&N survey scores were reduced from 32 at baseline to 20 at 1 month (adjusted p<0.001) and 26 at 3 months (adjusted p<0.001), but increased to 29, 30, and 27 at 6, 12, and 18 months, without significant differences as compared to baseline (adjusted p>0.38 for all).ConclusionsWe report high patient adherence and a 5% G-tube placement rate with exclusive meal replacement with Soylent in patients undergoing concurrent CRT for head and neck cancers.